Characterization of ultra-heat-treated whole milk in Tehran during their shelf life: Physicochemical changes, microbiological quality and sensory evaluation - SHAHBAZ, ARAMEH; Koushki, Mohammadreza; KHANNIRI, ELHAM; KHORSHIDIAN, NASIM (Indian Journal of Dairy Science, 2024)
In the present study, the physicochemical changes (titratable acidity, fat, density, and solids-not-fat), microbiological quality (total count), and sensory properties (odor, flavor, color, and overall acceptance) of whole ultra-heat-treated (UHT) milk marketed in Tehran, Iran were assessed during the storage period. Five brands of whole UHT milk were selected to determine the quality of the samples. The results showed that the acidity of UHT milk samples increased during storage, whereas the fat content decreased.  However, the titratable acidity and density of brands C and B respectively were not in accordance with the standard. Total bacteria count tests indicated that there was less than 10 cfu ⁄mL microorganism in UHT milk samples over storage time. All brands were similar in respect of color and flavor.  Although there was a decrease in sensory characteristics of UHT milk products during the storage period, they were organoleptically acceptable after six months of storage.